FLAG with Bortezomib in Children and Adolescents with Relapsed/Refractory Acute Myeloid Leukemia in a Resource-Limited Setting: A Single-Center Experience from India - Dave, Dipesh; Tak, Himangi; Trivedi, Maharshi; Yadav, Rajan; Doctor, Chinmay; Panchal, Harsha (South Asian Journal of Cancer, 2025)
The present study aimed to evaluate the impact, challenges, and outcome by adding bortezomib to the FLAG (fludarabine, cytarabine, and filgrastim) regimen in these populations in a resource-constraint setting.A prospective observational study was conducted at a tertiary cancer center in India from January 2022 to September 2024 involving patients diagnosed with relapsed/refractory acute myeloid leukemia (AML) receiving FLAG-bortezomib. Complete remission (CR) and associated toxicities were assessed.Out of 13 patients, 8 (61.53%) were males and 5 (38.46%) were females (range: 2–17 years). Sorafenib (n = 1) and midostaurin (n = 2) were given along with chemotherapy for children with FLT3 mutations. Myelosuppression was the most frequent toxicity, with all patients developing ≥ grade 3 pancytopenia. Five (38.46%) patients achieved CR after first cycle, two (15.39%) died during treatment, and six (46.15%) were with persistent leukemic activity. Median duration of neutrophil and platelet recovery was 22 (range: 6–65) and 24 (range: 5–70) days, respectively, in children who achieved CR. Median overall survival was 12 months. At the last follow-up, three (23.08%) patients are alive.FLAG-bortezomib regimen could help in pediatric and adolescent relapsed AML to achieve a remission comparable with other regimen in low- and middle-income countries, highlighting its potential.
Keywords: FLAG-bortezomib; pediatric AML; pediatric oncology; relapsed/refractory AML; salvage chemotherapy of relapsed AML